Theoretical model for the mechanical behavior of prestressed beams under torsion - Lopes, Sergio M. R. (2014)
In this article, a global theoretical model previously developed and validated by the authors for reinforced concrete beams under torsion is reviewed and corrected in order to predict the global behavior of beams under torsion with uniform longitudinal prestress. These corrections are based on the introduction of prestress factors and on the modification of the equilibrium equations in order to incorporate the contribution of the prestressing reinforcement. The theoretical results obtained with the new model are compared with some available results of prestressed concrete (PC) beams under torsion found in the literature. The results obtained in this study validate the proposed computing procedure to predict the overall behavior of PC beams under torsion.